Enhanced Structural, Thermal, and Electrical Properties of Multiwalled Carbon Nanotubes Hybridized with Silver Nanoparticles - Yusof, Y.; Zaidi, M.I.; Johan, M.R. (Hindawi Publishing Corporation, 2016)
The objective of this study is to evaluate the structural, thermal, and electrical properties of multiwalled carbon nanotubes (MWNT) hybridized with silver nanoparticles (AgNP) obtained via chemical reduction of aqueous silver salt assisted with sodium dodecyl sulphate (SDS) as stabilizing agent. Transmission electron microscopy (TEM) reveals microstructural analysis of the MWNT-Ag hybrids. The Fourier transform infrared (FTIR) spectra prove the interactions between the AgNP and carboxyl groups of the MWNT. Raman spectra reveal that the D- to G-band intensity ratios and increase upon the deposition of AgNP onto the surface of the MWNT. Thermogravimetric analysis (TGA) shows that the MWNT-Ag hybrids decompose at a much faster rate and the weight loss decreased considerably due to the presence of AgNP. Nonlinearity of current-voltage () curves indicates that electrical transport of pristine MWNT is enhanced when AgNP is induced as charge carriers in the MWNT-Ag hybrids. The threshold voltage value for the MWNT doped with a maximum of 70 vol% of AgNP was substantially reduced by 65% relative to the pristine MWNT. The MWNT-Ag hybrids have a favourable electrical characteristic with a low threshold voltage that shows enhancement mode for field-effect transistor (FET) applications.